THE CONSTRUCTION OF MASCULINITY IN SOCIAL MEDIA: A CRITICAL DISCOURSE ANALYSIS OF SOFT MASCULINITY AND UBERSEXUAL IN INDONESIAN TIKTOK CONTENT - Nabila, Clara Liza; Daulay, Harmona (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Masculinity is the result of gender construction originating from societal culture, where each society has a different culture. So these differences blend and create diverse types of masculinity. This research discusses two types of masculinity, namely soft masculinity and ubersexual. Soft maculinity emerged as a reaction to traditional, rigid masculinity norms. This type of man prioritizes empathy, emotional sensitivity, and also the courage to express his emotions openly. The TikTok content creator represents soft masculinity is Fahmi Nasrulloh who challenges patriarchal norms by showing that men can cook too. Meanwhile, ubersexual desribes men who are intellectual, confident, principled, as seen in Irwan, who is a TikTok content creator in the fields of politics, economis, and business. Through his TikTok content, he voiced his concern about corruption in Indonesia which is increasingly becoming an emergency. This research uses a critical discourse analysis methode with a qualitative approach. This type of research is descriptive, located on the tikTok platform. The results of the research show that the differences between the two types of masculinity lie in the approach to appearance, the values adhered to, behavioral patterns, relationships, and emotional expression. These two types show an evolution in the understanding of the role of men in society, and provide an idea of how a man should behave and interact in his environment. This research was conducted to determine the development of the construction of masculinity and see how the differences between the types of masculinity between soft masculinity and ubersexual are described